2022
DOI: 10.3390/genes13050866
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Genetic Diversity and Selection Signatures of the Endangered Kosovar Balusha Sheep Breed

Abstract: There is a growing concern about the loss of animal genetic resources. The aim of this study was to analyze the genetic diversity and potential peculiarity of the endangered Kosovar sheep breed Balusha. For this purpose, a dataset consisting of medium-density SNP chip genotypes (39,879 SNPs) from 45 Balusha sheep was generated and compared with SNP chip genotypes from 29 individuals of a second Kosovar breed, Bardhoka. Publicly available SNP genotypes from 39 individuals of the relatively closely located sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…These breeds have higher Ne 5 values, similar to Australian breeds (Ne from 140 to 348) [24], Russian breeds (Ne 5 from 65 to 543) [27], and some breeds in Kyrgyzstan (Gissar Ne 5 = 660 and Aykol Ne 5 = 563) [28]. The Ne 5 reported in our study for BA in Montenegro are significantly higher than those reported for Bardhoka (Bardoka) in Kosovo [35]. This may depend on the structure of the sampling flocks, related individuals, breed mixing, or migration, but also on the software used [55].…”
Section: Genetic Diversity Effective Population Size and Genome Inbre...supporting
confidence: 64%
See 3 more Smart Citations
“…These breeds have higher Ne 5 values, similar to Australian breeds (Ne from 140 to 348) [24], Russian breeds (Ne 5 from 65 to 543) [27], and some breeds in Kyrgyzstan (Gissar Ne 5 = 660 and Aykol Ne 5 = 563) [28]. The Ne 5 reported in our study for BA in Montenegro are significantly higher than those reported for Bardhoka (Bardoka) in Kosovo [35]. This may depend on the structure of the sampling flocks, related individuals, breed mixing, or migration, but also on the software used [55].…”
Section: Genetic Diversity Effective Population Size and Genome Inbre...supporting
confidence: 64%
“…The results for Montenegrin sheep for rarified allelic richness were higher than those reported by Deniskova et al (2018) [27] for Russian sheep breeds, Deniskova et al (2019) [28] for Kyrgyz sheep breeds, and Adeniyi et al (2022) [35] for Kosovar sheep breeds.…”
Section: Genetic Diversity Effective Population Size and Genome Inbre...mentioning
confidence: 53%
See 2 more Smart Citations
“…Four methods developed to identify selection signatures in livestock populations, all based on within-population approaches: i) extremely high SNP incidence in ROH ("extreme ROH islands" or "eROHi"), ii) integrated haplotype score (iHS), iii) number of segregating sites by length (nSL), and iv) composite likelihood ratio test (CLR), are widely used to identify hard and soft selection signals [ 12 18 ]. For example, many previous studies on Mediterranean sheep used statistical methods with medium density genomic data and found candidate genes for coat color, morphology, milk, and wool [ 19 24 ].…”
Section: Introductionmentioning
confidence: 99%